ROLE OF TRANSFORMATION LEADERSHIP ON STAFF PRODUCTIVITY IN THE INSURANCE INDUSTRY - Kajwang, Ben (Human Resource and Leadership Journal, 2022)
Purpose: The study examined the role of transformation leadership on staff productivity in the insurance industry. Materials and Methods: The research method used in this study involved the use of secondary data obtained from published studies, journals, articles and reports. This method was more preferred than conducting the actual field work since it saves time and reduces the cost of data collection. It is also easily accessible and convenient to use at any given time. Results: The findings of this study indicated that the empirical studies consisted of various research gaps including conceptual, contextual and geographical gaps. This is because some of the studies focused more on the influence and effects of transformational leadership on employee performance, innovation behaviour, organizational learning, organizational commitment rather than on employee productivity. On the other hand, the findings of other studies discussed on other leadership styles apart from transformational leadership while most of the studies were conducted outside Kenya. Recommendations: The findings of this study will be applicable to a wide range of industry players in the insurance sector. The management of insurance companies will benefit from this study since it clarifies the significance of transformational leadership and its function in enhancing employee productivity in the insurance sector. The policymakers in the insurance will also benefit from this study especially when implementing policies with regards to improving the productivity of employees and empowering managers and leaders. Further, this study will also be relevant to the researchers and academicians since it will be used to add up to their literature work and will also motivate them to carry out more research related to the current topic so as to address some of the research gaps identified in this study.